Growth Rate of Escherichia coli at Elevated Temperatures: Limitation by Methionine - Ron, Eliora Z. (J Bacteriol, 1971)
When Escherichia coli growing in minimal medium is shifted from 37 C to any temperature in the range 40 to 45 C, the growth rate immediately assumes a new, lower value, characteristic of that temperature. The decrease is shown to be due, in several strains, to decreased activity of the first enzyme of the methionine pathway, homoserine trans-succinylase, which thus appears to be more heat-sensitive than any other essential enzyme in the cell. This sensitivity does not involve progressive denaturation of the enzyme; rather, the response to a shift of temperature, in either direction, is immediate and reversible.